KAJIAN TEKNOLOGI PENGOLAHAN AIR LIMBAH RUMAH SAKIT DAN SNI TERKAIT - Waluyo, Prihadi (Center for Environmental Technology, 2009)
The study of hospital waste water treatment technology, with choice one ofÃ‚Â waste water treatment technology this is activated sludge process, which already common use related to the National Standard of Indonesia (SNI) about environment, especially waste water, and more specifically is activated sludge. These snis are used to compliment of testing from technology of hospital waste water treatment. There for, it is need to be more reinforce the application of SNI so that each the technical regulation donÃ¢â‚¬â„¢t want to detail the technical aspect it self. This because to revise the legal regulation is not easy, meanwhile the SNI can be revised anytime we need. We need to continue and to increase cooperation (MOU) between the Ministry of Environment and the National Accreditation Committee (KAN), about the joint assessment accreditation of environment parameters quality laboratory. The good application of technology and standard will have a good impacts for the growth of economic environment equipments industry. From the hospital waste water samples in Jakarta has showedÃ‚Â that the chemical consentrate pollution very fluctuated, e.g.,Ã‚Â BOD 31,52 - 675,33 mg/l, ammoniac 10,79 - 158,73 mg/l, detergent (MBAS) 1,66 - 9,79 mg/l. From the BOD (mg/l) parameter with minimum 31, 52 and maximum 675,33 still include in the BOD parameter, as decree of KLH No 58/95, mentioned that the maximum gradient 75 mg/l, but to see from the mean as 353,43 are far out from the article of Ã‚Â KLH decree. Ã‚Â Key words : Air limbah, lumpur aktif, teknologi, SNI, lingkungan, standardisasi